Dihydromyricetin enhances the osteogenic differentiation of human bone marrow mesenchymal stem cells in vitro partially via the activation of Wnt/β‐catenin signaling pathway. (24th August 2016) - Zhang, Wei; Wang, Shengdong; Yin, Houfa; Chen, Erman; Xue, Deting; Zheng, Qiang; Gao, Xiang; Pan, Zhijun
Abstract: Substantial evidence has demonstrated that the decreased osteogenic differentiation of bone mesenchymal stem cells (BMSCs) is closely related to bone metabolic diseases. Thus, it is very important to develop several potentially useful therapeutic agents to enhance BMSC osteogenesis. Flavonoids show promise in enhancing bone mass. Dihydromyricetin (DMY), a type of flavonoid, has not yet been investigated regarding its effects on BMSC osteogenesis. To investigate the effects of DMY on osteogenesis, human BMSCs were induced with or without DMY. We found that DMY (0.1–50 μm ) exhibited no cytotoxic effect on proliferation, but increased alkaline phosphatase activity, osteoblast‐specific gene expression, and mineral deposition. It also enhanced active β‐catenin expression and reduced dickkopf‐1(DKK1) and sclerostin expression. The Wnt/β‐catenin signaling pathway inhibitor (DKK1 and β‐catenin‐specific siRNA) decreased the enhanced bone mineral formation caused by DMY. Taken together, these findings reveal that DMY enhances osteogenic differentiation of human BMSCs partly through Wnt/β‐catenin in vitro.